Coevolution of aah: A dps-Like Gene with the Host Bacterium Revealed by Comparative Genomic Analysis. (1st February 2012) - Ping, Liyan; Platzer, Matthias; Wen, Gaiping; Delaroque, Nicolas
Abstract : A protein named AAH was isolated from the bacterium Microbacterium arborescens SE14, a gut commensal of the lepidopteran larvae. It showed not only a high sequence similarity to Dps-like proteins (DNA-binding proteins from starved cell) but also reversible hydrolase activity. A comparative genomic analysis was performed to gain more insights into its evolution. The GC profile of the aah gene indicated that it was evolved from a low GC ancestor. Its stop codon usage was also different from the general pattern of Actinobacterial genomes. The phylogeny of dps -like proteins showed strong correlation with the phylogeny of host bacteria. A conserved genomic synteny was identified in some taxonomically related Actinobacteria, suggesting that the ancestor genes had incorporated into the genome before the divergence of Micrococcineae from other families. The aah gene had evolved new function but still retained the typical dodecameric structure.